Torsion-Driven Plectoneme Formation During Nanopore Translocation of DNA Polymers - Fei Zheng; Antonio Suma; Christopher Maffeo; Kaikai Chen; Mohammed Alawami; Jingjie Sha; Aleksei Aksimentiev; Cristian Micheletti; Ulrich F. Keyser (Physical Review X)
The transport of DNA polymers through nanoscale pores is central to many biological processes, from bacterial gene exchange to viral infection. In single-molecule nanopore sensing, the detection of nucleic acid and protein analytes relies on the passage of a long biopolymer through a nanoscale aperture. Understanding the dynamics of polymer translocation through nanopores, especially the relation between ionic current signal and polymer conformations, is thus essential for the successful identification of targets. Here, by analyzing ionic current traces of dsDNA translocation, we reveal that features up to now uniquely associated with knots are instead different structural motifs: plectonemes. By combining experiments and simulations, we demonstrate that such plectonemes form because of the solvent flow that induces rotation of the helical DNA fragment in the nanopore, causing torsion propagation outwards from the pore. Molecular dynamic simulations reveal that plectoneme nucleation is dominated by the applied torque, while the translocation time and size of the plectonemes depend on the coupling of torque and pulling force, a mechanism that might also be relevant for in vivo DNA organization. Experiments with nicked DNA constructs show that the number of plectonemes depends on the rotational constraints of the translocating molecules. Thus, our work introduces plectonemes as essential structural features that must be considered for accurate analysis of dsDNA polymers in the nanopore.